PENYULUHAN TENTANG BAHAN AJAR LITERASI BERBASIS KEARIFAN LOKAL DI SDN 2 TUGU MULYA - Ifah, Ifah Hanifah; Asep Jejen Jaelani; Sun Suntini (Kilau Publishing, 2023)
This community service is an extension and training for elementary school teachers at SDN 2 Tugumulya Kecamtan Darma, Kuningan Regency, on the preparation of literacy teaching materials based on local wisdom. This is based on the fact that students' literacy skills are still low, and one of the factors is the lack of teaching materials. This service uses the method of counseling and training with the following stages; 1) planning, 2) implementation, 3) evaluation, 4) mentoring and consultation. After being given material on literacy concepts and teaching materials, the teacher's understanding is getting better. This can be seen from the question and answer activities carried out. In addition, the teacher's ability to compile simple teaching materials is good. They can choose the right material, and evaluate it according to the specified literacy criteria.